2023
DOI: 10.1158/1078-0432.c.6523526
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Data from Extracellular Lumican Inhibits Pancreatic Cancer Cell Growth and Is Associated with Prolonged Survival after Surgery

Abstract: <div>Abstract<p><b>Purpose:</b> To evaluate the relevance between lumican expression patterns and the clinical course of patients with pancreatic ductal adenocarcinoma (PDAC), and to investigate the role of lumican in PDAC progression.</p><p><b>Experimental Design:</b> One hundred thirty-one patient tumors were chosen for tissue microarray staining, and Cox regression analysis was used to test the associations between lumican expression and clinical, pathologic, … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
0
0
0
Order By: Relevance
“…Previous studies (Li et al, 2014;Zhang et al, 2016) reported that LUM is the most abundant protein polysaccharide in BRCA, and LUM expressions in cancer cells are high. Wang et al reported that LUM expressions are strongly upregulated in STAD (Wang et al, 2017).…”
Section: Figurementioning
confidence: 97%
See 2 more Smart Citations
“…Previous studies (Li et al, 2014;Zhang et al, 2016) reported that LUM is the most abundant protein polysaccharide in BRCA, and LUM expressions in cancer cells are high. Wang et al reported that LUM expressions are strongly upregulated in STAD (Wang et al, 2017).…”
Section: Figurementioning
confidence: 97%
“…Our diffuse analysis revealed that LUM levels are elevated in advanced BLCA, ESCA, KIRC, OV, and THCA patients. Moreover, LUM protein levels are highly elevated in gastric cancer (Chen et al, 2017), colon cancer (Seya et al, 2006;de Wit et al, 2013) and pancreatic cancer (Li et al, 2014). In general, protein expressions reflect LUM activities.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation